RF/DC 스퍼터 성장한 ITO/Ag/ITO 투명전극 박막의 특성 연구 - 이영재(Youngjae Lee); 김제하(Jeha Kim) (Current Photovoltaic Research, 2022)
We investigated the optical and electrical characteristics of ITO/Ag/ITO (IAI) 3-layer thin films prepared by using RF/DC sputtering. To measure the thickness of all thin film samples, we used scanning electron microscopy. As a function of Ag thickness we characterized the optical transmittance and sheet resistance of the IAI samples by using UV-Visible spectroscopy and Hall measurement system, respectively. While the thickness of both ITO thin films in the 3-layered IAI samples were fixed at 50 nm, we varied Ag layer thickness in the range of 0 nm to 11 nm. The optical transmittance and sheet resistance of the 3-layered IAI thin films were found to vary strongly with the thickness of Ag film in the ITO (50 nm)/Ag(t0)/ITO (50 nm) thin film. For the best transparent conducting oxide (TCO) electrode, we obtained a 3-layered ITO (50 nm)/Ag (t0 = 8.5 nm)/ITO (50 nm) that showed an avrage optical transmittance, AVT = 90.12% in the visible light region of 380 nm to 780 nm and the sheet resistance, R□＝7.24 Ω/□. KCI Citation Count: 0